Socioeconomic Impact of Biogas on Padampur VDC in Chitwan, Nepal - Amgai, Krishna Prasad (The Third Pole: Journal of Geography Education, 2014)
Biogas as a new and modern alternative energy resource generated within the households of the rural premise is studied in order to assess the socio-economic condition of the users. The study was carried out in the Padampur VDC of Chitwan District in 2010. The study is based on a sample of 35 biogas users (14 percent of the installed plant). The study found that the use of biogas energy has saved 80 percent of fuel wood and kerosene consumption and 50 percent use of electricity in the households surveyed. Likewise, the use of biogas effluent, by-product from the domestic plant, is proved useful as bio-fertilizer in the agriculture field. More than 71 percent biogas users found increase in their agricultural production. Thus, the installation of biogas has brought some positive changes in health, hygiene and the sanitation including household income. DOI: http://dx.doi.org/10.3126/ttp.v11i0.11525 The Third Pole Vol. 11-12, 2012 page:16-20